(untitled) (Journal of Forest and Livelihood, 2024)
The author highlights various forms of protection arrangements being practiced in community forestry in Nepal, and identifies factors inducing innovations in forest protection. She highlights that still a huge amount of FUG efforts and resources is being allocated for protection of forests, and indicates a possibility of reducing such costs where all FUG members abide by the rules of forest utilization.